Passion fruit seed meal at growing and finishing pig (30-90 kg) feeding - Perondi, Dani [UNESP]; Moreira, Ivan; Pozza, Paulo Cesar; Carvalho, Paulo Levi de Oliveira; Pasquetti, Tiago Junior; Huepa, Laura Marcela Diaz (Editora da Universidade Federal de Lavras, 2014)
The passion fruit seed is a byproduct of the extraction of the passion fruit pulp and can be used for feeding to pigs. Two experiments were conducted (digestibility and performance) to evaluate the use of the passion fruit seed meal in feed for growing and finishing pigs. A digestibility trial was conducted with growing and finishing pigs, in which the passion fruit seed meal (PSM) replaced the reference diet (0% PSM) in levels of 4, 8, 12 and 16%. Thirty barrows were used with average weight of 36.85±4.19. The PSF showed DE and ME of 3.244 and 3.223 Mcal/kg, respectively. In the performance trial, were used 150 pigs, which 75 in the growing phase and 75 pigs in the finishing, with initial body weight of 30.63±1.49 and final of 60.38±4.75 kg and 60.40±1.50 and 90.02±4.84 kg, respectively. Five diets were used, with four inclusion levels of PSM (4, 8, 12 e 16%) and one control diet (0% of PSM). The PSM levels did not influence (P>0.05) the performance variables. In the growing pigs, serum levels of cholesterol increased linearly with (P<0.05) inclusion levels of PSM. Quantitative of carcass traits and meat quality were not affected (P>0.05) by increasing levels of PSM in the diets. We conclude that the PSM can be used up to 16% in growing and finishing pigs diets.

A semente do maracujá é um subproduto da extração da polpa do maracujá, podendo ser utilizado na alimentação dos suínos. Foram conduzidos dois experimentos (digestibilidade e desempenho), objetivando avaliar a utilização do farelo da semente de maracujá na alimentação de suínos em crescimento e terminação. Inicialmente foi realizado um ensaio de digestibilidade com suínos em crescimento e terminação, em que o farelo da semente de maracujá (FSM) substituiu a ração referência (0% FSM) em níveis de 4, 8, 12 e 16%. Foram utilizados 30 suínos, machos castrados, com peso vivo médio inicial de 36,85±4,19. O FSM apresentou ED e EM de 3.244 e 3.223 Mcal/kg, respectivamente. No ensaio de desempenho, foram utilizados 150 suínos, sendo 75 na fase de crescimento e 75 na fase de terminação, com peso vivo inicial de 30,63±1,49 e final de 60,38±4,75 kg e 60,40±1,50 e 90,02±4,84 kg, respectivamente. Foram utilizadas cinco dietas, sendo quatro níveis de inclusão do FSM (4, 8, 12 e 16%) e uma ração testemunha (0% do FSM). Os níveis do FSM não influenciaram (P>0,05) as variáveis de desempenho. Na fase de crescimento, os níveis séricos de colesterol aumentaram linearmente (P<0,05) com os níveis de inclusão do FSM. As variáveis quantitativas de carcaça e qualitativas da carne não foram influenciadas (P>0,05) pelos níveis crescentes do FSM nas dietas. Conclui-se que o FSM pode ser utilizado em até 16% em dietas de suínos em crescimento e terminação.
Farelo da semente de maracujá na alimentação de suínos em crescimento e terminação (30-90 kg)
Keywords: Co-product; digestibility; nutritional value; carcass; Subproduto; digestibilidade; valor nutricional; carcaça